Rancang Bangun Sistem Informasi Akuntansi Penerimaan Aliran Kas Distribusi Beras Miskin - Dina, Fara; Ismail, Herlina (Disclosure: Journal of Accounting and Finance, 2023)
In this globalization era, information technology is accelerates. Computers which are tools will create to take it easy of human work, when achieving progress both in the manufacture of hardware and software. Information system design is the best solution to solve problems that exist in this agency, and with a computerized system can achieve an effective and efficient activity in supporting activities in this agency. A computerized system is better than a manual system so that it runs more effectively and efficiently as well as a more conducive reception system compared to the previous system. This study uses quantitative methods and system development in the form of methods in analyzing the designed software. From the results of this study it is hoped that it can help the performance of village agencies starting from inputting data to distributing it to the community.